(untitled) (Indian Journal of Arid Horticulture, 2025)
The five plants in each progeny of F, from a cross PSB-1 x KT-9 were selected. These plants were bud and mix pollinated (BP & MP) to produce bud and mix pollinated seeds of F, i.e. F. The materials thus, developed were evaluated in compact family block design with three replications for eight horticultural and three quality traits. F, 11-119-BP, F, 11- 111-BP, F, 11-113-BP, F, 5-109-BP and F, 2-77-BP and F, 4-92-MP, F, 4-94-MP, F, 11-120-MP, F, 3-84-MP and F, 11- 112-MP possessed good yield and quality traits. PCV & GCV was high for the gross curd weight, net curd weight and harvest index. These three characters also exhibited high heritability and genetic advance as percentage of mean indicating the additive gene effects for these traits. The high heritability with low to moderate genetic advance was found for stalk length and days to harvesting.